1995
DOI: 10.1093/oxfordjournals.eurheartj.a060795
|View full text |Cite
|
Sign up to set email alerts
|

Is the clinical spectrum and prognosis of native valve infective endocarditis in non-addicts changing?

Abstract: One hundred and ninety-four episodes of endocarditis on native valves in non-addict patients were diagnosed from 1975 to 1992 and were divided into groups A (78 patients, 1975-1983) and B (116 patients 1984-1992). Both groups had the same gender distribution, similar valvular involvement and microbiological characteristics. In group B patients, median age was older (46 vs 54 years, P = 0.0002), the number of patients without previous heart disease was higher (46% vs 22%, P = 0.02) and the median time of sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Increasing age of patients of IE in west is attributable to; markedly decrease frequency of RHD, 12 longer survival of patients with valve disease and CHD because of readily available modern medical and surgical therapy, increased incidence of degenerative valvular disease, 2 aging of the population in general 9,13 and more frequent use of invasive central vascular catheters which are associated with an increase in nosocomiallyacquired endocarditis. There was a significant rise in the age of the patients during the 1940s ,1950s and 1960s 14 and studies covering the time periods 1968-1973, 15 1973-1984 16 and 1970-1977 17 found the mean age to lie within the sixth decade. Our findings suggest that there has been no further increase in the age of the patients and concur with two recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age of patients of IE in west is attributable to; markedly decrease frequency of RHD, 12 longer survival of patients with valve disease and CHD because of readily available modern medical and surgical therapy, increased incidence of degenerative valvular disease, 2 aging of the population in general 9,13 and more frequent use of invasive central vascular catheters which are associated with an increase in nosocomiallyacquired endocarditis. There was a significant rise in the age of the patients during the 1940s ,1950s and 1960s 14 and studies covering the time periods 1968-1973, 15 1973-1984 16 and 1970-1977 17 found the mean age to lie within the sixth decade. Our findings suggest that there has been no further increase in the age of the patients and concur with two recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of patients without clear underlying diseases predisposing to IE has risen from around 5% in a Taken prior to the initiation of antibiotic therapy (not available for 8 cases) b No preantbiotic blood culture data was available for eight cases c Calculated by dividing the number of positive blood culture sets by the total number of sets taken in each group d Denotes the frequency of detecting at least one positive blood culture from those taken von Reyn's landmark study [9], using strict case definitions, to around 35-45% [7,10,16,18]. This category seems to include many elderly patients who are at risk for degenerative valvular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The in-hospital mortality from endocarditis has over recent decades commonly been reported to be 20 Á25% [1], although some investigations suggest a decrease in mortality [2]. Thus, a recent Danish investigation from a secondary centre found a mortality of 14% [3].…”
Section: Introductionmentioning
confidence: 99%